EMU and macroeconomic shocks: some evidence on Spanish regions - Adolfo Maza; Blanca Sanchez-Robles (European Regional Science Association (ERSA), 2002)
According to the Theory of Optimal Currency Areas, one of the main costs that EMU may entail for countries and regions belonging in it is the loss of monetary autonomy at the country level. In fact, the scenario brought about by the single currency does not allow for domestic policy adjustments (i.e a change in the exchange rate or a specific monetary measure) in response to shocks. The importance of this cost, in turn, is related to the nature of shocks impinging over the different countries and regions that encompass the eurozone. If the probability that countries and regions suffer the same sort of shock is large, then a common policy designed by the ECB will have beneficial effects on the whole eurozone. Instead, if regions or countries are likely to be exposed to different kinds of shocks, then the common monetary policy will benefit some areas in detriment of others. To address this issue empirically, this paper focuses in the analysis of the shocks that have hit the Spanish regions in the recent past. In particular, we want to identify the kind of shocks that have been suffered by the Spanish regions in the last decades, distinguishing several categories: symmetric versus asymmetric, persistent versus transitory and demand shocks versus supply shocks. By symmetric shocks we understand those that have similar impact on all regions. Permanent shocks are those characterised by side effects that do not vanish in the short run. An example of a demand shock is a change in consumers' preferences, whereas a supply shock is typically a modification in the price of a raw material. We examine the behaviour of GAV and prices for 17 Spanish regions over the period 1955-97. In particular, we write a baseline model in the form of the state-of-spaces, in order to be able to apply the Kalman filter. Main conclusions are as follows: first, and employing the assumption that common shocks are tantamount to symmetric shocks, it seems that, in most cases, the shocks that have affected the Spanish regions have been mostly symmetric, while asymmetric shocks have been more sparse. Second, empirical results suggest that the effects of these shocks have been, generally speaking, persistent rather than transitory. Finally, the estimation suggests that supply shocks have been slightly more frequent that demand shocks. The policy implications of these results are that the lack of monetary autonomy and the loss of the exchange rate as adjustment mechanisms may not be very onerous. The common monetary policy implemented by the ECB will probably have similar effects on all Spanish regions. Therefore, the danger of an increase in regional disparities via this channel do not seem to be very severe.
Keywords: 330